2019
DOI: 10.3390/ijerph16142488
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Clusters of Children with Cleft Lip and Palate and Their Association with Polluted Zones in the Monterrey Metropolitan Area

Abstract: This study examines the spatial structure of children with cleft lip and palate (CLP) and its association with polluted areas in the Monterrey Metropolitan Area (MMA). The Nearest Neighbor Index (NNI) and the Spatial Statistical Scan (SaTScan) determined that the CLP cases are agglomerated in spatial clusters distributed in different areas of the city, some of them grouping up to 12 cases of CLP in a radius of 1.2 km. The application of the interpolation by empirical Bayesian kriging (EBK) and the inverse dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…In context of emerging clusters sharing municipalities from different states, coordinated efforts among various governments levels are critical. Past published research has shown the advantages of these type of coordinated public policy interventions not only to prevent the spread of sexual transmission diseases (Marotta, 2016) or Salmonella (Seixas et al, 2018) but also to provide with better healthcare services to vulnerable population suffering from cleft lip and palate (Gasca et al, 2019), obesity (Gartner et al, 2016), tuberculosis (Rao et al, 2017), and so forth.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…In context of emerging clusters sharing municipalities from different states, coordinated efforts among various governments levels are critical. Past published research has shown the advantages of these type of coordinated public policy interventions not only to prevent the spread of sexual transmission diseases (Marotta, 2016) or Salmonella (Seixas et al, 2018) but also to provide with better healthcare services to vulnerable population suffering from cleft lip and palate (Gasca et al, 2019), obesity (Gartner et al, 2016), tuberculosis (Rao et al, 2017), and so forth.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…In the context of emerging clusters of municipalities from different states, coordinated efforts among various government levels are critical. Past published research has shown the advantages of this type of coordinated public policy intervention not only to prevent the spread of sexual transmission diseases ( Marotta, 2016 ) or Salmonella ( Seixas et al, 2018 ) but also to provide better healthcare services to vulnerable populations suffering from cleft lip and palate ( Gasca et al, 2019 ), obesity ( Gartner et al, 2016 ), tuberculosis ( Rao et al, 2017 ), and so forth.…”
Section: Discussionmentioning
confidence: 99%
“… Bolaño-Ortiz et al, 2020 ; Gasca-Sanchez et al, 2019 ; ILO (International Labour Organization), 2018 ; Jackman et al, 2015 ; Millett et al, 2020 ; OECD (Organisation for Economic Co-operation and Development), 2019 ; Yi et al, 2021 ; Yin et al, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…After processing the information, the degree of concentration of the companies with information on polluting substances and BC cases was determined using the NNI proposed by Clark and Evans (1954) . There are some investigations in which this technique was used to determine the degree of concentration of points over space and to identify clusters ( Boix et al., 2015 ; Gasca-Sanchez et al., 2019 ; Meyer, 2006 ).…”
Section: Methodsmentioning
confidence: 99%